A computer program for the analysis of space truss - Aganistapichat, Atichat (1976)
This thesis is an effort to furnish a computer program for the analysis of space truss structures, by stiffness method. This space truss structure analyzed by this computer program are limited to trusses having 1) straight and prismatic members; 2) loads applied on ball-socket-ended members limited only to those given in Appendix B. The following secondary effects are taken into account: a. temperature changes b. support displacements c. prestrains.